Career Satisfaction of Islamic Guidance and Counseling Teachers: Addition of Gratitude Variables to Greenhaus Theory - Cucu Arumsari; Uman Suherman; Juntika Nurihsan; Yusi Riska Yustiana; Eko Yulianto (STAI Hubbulwathan Duri, 2025)
Greenhaus’s Theory assesses career satisfaction through five key dimensions: career achievement, goal fulfillment, income, career advancement, and skill development. However, in the context of Islamic guidance and counseling teachers, gratitude should be considered as an additional determinant. Gratitude, as a core spiritual value, plays a significant role in career satisfaction for Muslim educators, yet it is often overlooked in traditional career satisfaction models. This study aims to expand Greenhaus’s Theory by incorporating gratitude as a sixth dimension. A quantitative approach was applied using Confirmatory Factor Analysis (CFA) with SmartPLS to validate the six-dimensional career satisfaction model. A random sample of 121 Islamic guidance and counseling teachers from Tasikmalaya participated in the study by completing a career satisfaction questionnaire. The findings confirm that career achievement, goal fulfillment, income, career progress, skill development, and gratitude are all valid and reliable indicators of career satisfaction. Gratitude significantly contributes to teachers’ overall career fulfillment, reinforcing its importance as a spiritual dimension in career satisfaction models. The inclusion of gratitude enhances the applicability of Greenhaus’s model in Islamic cultural contexts, addressing the gap in traditional career satisfaction frameworks. Recognizing gratitude as a career satisfaction factor provides a more comprehensive understanding of teacher well-being in religiously influenced educational environments. The adaptation of Greenhaus’s Theory with the inclusion of gratitude offers a more holistic perspective on career satisfaction for Islamic educators. Future research should explore its implications across diverse cultural and religious settings.